Kyste De L’ouraque Infecte : A Propos De Trois Cas Cliniques Au Chu De Parakou Au Benin - Hodonou Montcho Adrien; Allodé Salako Alexandre; Tamou sambo Bio; Ossé Martin; Moumouni Amina; Mensah Emile; Mehinto Kouassi Delphin (European Scientific Journal, ESJ, 2016)
Bacground: The urachus is a fibrous remnant of the allantois. That connects the bladder dome to the anterior abdominal wall. After birth it is obliterated in general. In some cases it may persist as cyst , fistula , sinus or diverticulum. This persistence of the urachus often is signaled by a complication. Infection is the most common complication and the most dangerous is his degeneration. The infection can be misunderstood and confused with other pathologies of the navel. Methods: Our study reports three clinical cases of infected urachal cyst. Result: these report cases illustrate the need to think of this diagnosis before the painful of the navel and abdomen. The ultrasound examination can help for the diagnosis.